Protagonistas para o mundo: adequações do mercado escolar às novas aspirações de acesso ao ensino superior pelas elites - Bruna de Figueiredo Caldeira (2019)
The main goal of this research is to investigate the educational market adequacies of Belo Horizonte regarding the new access aspirations to higher education by the elite. The affirmative action policies conducted in Brazil since 2000 have in some way, affected Brazilian elite groups, considering that their opportunities to get into public universities have decreased. Despite the difficulties in evaluating the effects of these policies some tendencies have already been discussed in studies. Amongst them, it can be highlighted the strategies of the education internationalization employed by these families, and the choice criteria refinement of the higher education establishment. The thematic has been treated in a way to observe the specific strategies, the subjects that reproduce it, the impact and the consequences of the choice strategies of educational institutions and internationalization. In this work, the investigation will take place in the perspective of the strategies reinforcement by the educational institutions which serve these elite. The research presents two phases, the first being the exploratory study of 11 basic education schools in Belo Horizonte, which serve the upper middle class families and the second, the case study in one of these institutions. The fundamental axis in the first stage is to characterize the schools, according to the infrastructure data of the Censo Escolar da Educação Básica, the Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira (Inep) and the pedagogical proposals of the schools. In addition, it was also carried out an investigation regarding the motivation for the enrollment in higher education institutions (HEI) with the students of these 11 schools through a contextual questionnaire of the Exame Nacional do Ensino Médio (Enem) of 2016. The second stage contemplates the application of the questionnaire to high school students of the analyzed school and the pedagogical coordinators interviews. Based on the case study, the objective was to describe these students profile, analyze the preferences and the choice criteria for admission to HEI, and analyze the school's adaptations to the new interests of its students. The results showed the schools strategies for the adequacy of their educational offers, mainly from the internationalization programs elaborated with emphasis on foreign language certification by prestigious universities abroad, curriculum adaptation to the bilingual program, offer of cultural exchanges, partnerships with outsourced companies for orientation in the external entrance examinations, among others. The collected data evidenced the discourses based on the protagonism promotion of their students to the world which, to a certain extent, reinforces the elements of distinction of the elite in the educational structure. Therefore, this work contributes to the debates regarding the elite segments strategies to maintain their power, and their consequences for the educational stratification.